Heterogeneous nuclear ribonucleoprotein hnRNPA2/B1 regulates the abundance of the copper-transporter ATP7A in an isoform-dependent manner - McCann, Courtney J.; Hasan, Nesrin M.; Padilla-Benavides, Teresita; Roy, Shubhrajit; Lutsenko, Svetlana (Frontiers in Molecular Biosciences, 2022)
Copper (Cu) is an essential micronutrient with a critical role in mammalian growth and development. Imbalance of Cu causes severe diseases in humans; therefore, cellular Cu levels are tightly regulated. Major Cu-transport proteins and their cellular behavior have been characterized in detail, whereas their regulation at the mRNA level and associated factors are not well-understood. We show that the heterogeneous nuclear ribonucleoprotein hnRNPA2/B1 regulates Cu homeostasis by modulating the abundance of Cu(I)-transporter ATP7A. Downregulation of hnRNPA2/B1 in HeLa cells increases the ATP7A mRNA and protein levels and significantly decreases cellular Cu; this regulation involves the 3’UTR of ATP7A transcript. Downregulation of B1 and B1b isoforms of hnRNPA2/B1 is sufficient to elevate ATP7A, whereas overexpression of either hnRNPA2 or hnRNPB1 isoforms decreases the ATP7A mRNA levels. Concurrent decrease in hnRNPA2/B1, increase in ATP7A, and a decrease in Cu levels was observed in neuroblastoma SH-SY5Y cells during retinoic acid-induced differentiation; this effect was reversed by overexpression of B1/B1b isoforms. We conclude that hnRNPA2/B1 is a new isoform-specific negative regulator of ATP7A abundance.